Analisis Analisis Implementasi Pendekatan Etnosains dalam Pembelajaran IPA - Danang Habib Pratama; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
Content analysis research aims to provide a literature review in the use of ethnoscince approaches in science learning. This analytical research uses a descriptive analysis method with a qualitative approach. Article documents were obtained through the Google Schoolar and Sinta pages using the keywords "ethnoscience approach in science learning" and "ethnoscience-based science learning" in the range of 2017 to 2023. After going through the selection stage of several journal articles, 20 articles were found to be analyzed. The results of the analysis show that the implementation of the ethnoscience approach in junior high school science learning is effective in improving various abilities and skills of students such as thinking abilities, problem solving abilities, process skills and scientific literacy.